2007
DOI: 10.1021/ja0650450
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Intermolecular Amination of C−H Bonds: Method Development and Mechanistic Insights

Abstract: Reaction methodology for intermolecular C-H amination of benzylic and 3 degrees C-H bonds is described. This process uses the starting alkane as the limiting reagent, gives optically pure tetrasubstituted amines through stereospecific insertion into enantiomeric 3 degrees centers, displays high chemoselectivity for benzylic oxidation, and enables the facile preparation of isotopically enriched 15N-labeled compounds. Access to substituted amines, amino alcohols, and diamines is thereby made possible in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
204
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(225 citation statements)
references
References 25 publications
14
204
1
6
Order By: Relevance
“…In our experience, the oxidation of substrate by Rh-nitrene 6 seems to correlate with competitive formation of a mixed-valent (Rh 2+ /Rh 3+ ) dimer 8 that visibly colors the reaction solution red. Previous studies show that this red species is generated when Rh 2 (esp) 2 1, sulfamate 2, and oxidant 3 are mixed in solution (e.g., 0.3 mM 1 in chlorobenzene) (4,5,11). In this report, we provide direct evidence for the formation of species 8.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…In our experience, the oxidation of substrate by Rh-nitrene 6 seems to correlate with competitive formation of a mixed-valent (Rh 2+ /Rh 3+ ) dimer 8 that visibly colors the reaction solution red. Previous studies show that this red species is generated when Rh 2 (esp) 2 1, sulfamate 2, and oxidant 3 are mixed in solution (e.g., 0.3 mM 1 in chlorobenzene) (4,5,11). In this report, we provide direct evidence for the formation of species 8.…”
supporting
confidence: 59%
“…mass spectrometry | transient intermediates | C-H oxidation | catalysis C atalytic methods for selective C-H oxidation rely on the exquisite choreography of a series of ligand substitution and redox events (1,2) and in some instances, the controlled generation of a hyperreactive electrophile (3)(4)(5). The Du Bois laboratory has developed an amination protocol that uses the catalyst bis [rhodium(α,α,α′,α′-tetramethyl-1,3-benzenedipropionic acid)], hereafter designated as Rh 2 (esp) 2 , to promote both intra-and intermolecular oxidation reactions (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Du Bois and colleagues have developed a bridged achiral rhodium catalyst Rh 2 (esp) 2 that has performed well at low catalyst loadings in both intra-and intermolecular C2H amination reactions (Fig. 12) [83][84][85] . Enantioselective intermolecular reactions of metal nitrenes are less developed than the parallel reactions of metal carbenes, although some significant examples have been reported 81,82,86,87 .…”
Section: C-h Functionalization By Metal Nitrenoidsmentioning
confidence: 99%
“…The reaction was further explored by investigating other hypervalent iodine(III) reagents (Scheme 2). [16] It was found that the reaction of 1a with PhI(OPiv) 2 or PhI(OBz) 2 furnished the corresponding α-t-butylcarbonyloxy ketone 4 and α-benzoyloxy ketone 5 in 86% and 89% yield, respectively [Eq. (1) and (2)].…”
Section: Resultsmentioning
confidence: 99%